Stories that Move with Pedagogy students at the University of Barcelona: Experience and research regarding self-education, coeducation and alter-education - Assumpta Aneas Alvarez; Núria Lorenzo Ramírez; Monica Ferré Tobaruela; Anna Aroca Seró (Revista Catalana de Pedagogia, 2024)
This article presents the experience of the implementation of the Project Stories that Move (StM), Stories that move, in the Degree in Pedagogy of the University of Barcelona, as well as the research carried out as a result of this implementation. The aim is to introduce and explore the tool, collect narrative information to assess whether the proposal is eco-pedagogical.  Students analyze the tool and produce a narrated work. The student narratives are analyzed qualitatively with the NVivo program. It shows how StM allows us to work on issues related to self-education, coeducation and altereducation. Both the students' narratives and the theoretical framework underpinning ecopedagogy and the tool itself for to combat discrimination show that it is urgent to work in this direction in order to achieve the Sustainable Development Goals, a critical, empowered youth committed to society and the land it inhabits.